Nonlinear Adjustment towards Purchasing Power Parity in ASEAN Exchange Rates - Liew, Venus Khim-Sen; Ahmad Zubaidi, Baharumshah; Lau, Evan (IUP Publications, 2004)
The major finding of this study is that the long run purchasing power parity (PPP) deviations of the major ASEAN exchange rates exhibit nonlinear adjustment which may be characterised by the Smooth Transition Autoregressive (STAR) model. This finding warrants us that policy decision based on inappropriate linear studies may not be effectiveness. Besides, exchange rates with deviations with higher speed of adjustment are found to be more pruned to currency crisis.